2016
DOI: 10.1177/1461444816649922
|View full text |Cite
|
Sign up to set email alerts
|

Private practice: Using digital diaries and interviews to understand evangelical Christians’ choice and use of religious mobile applications

Abstract: Religious mobile applications (apps) offer a relatively new space for religious practices such as studying sacred texts, prayer, and meditation. To date, most studies in the digital religion literature, and to some extent in general mobile app studies, focus inquiry on app content and/or design only. This study advances these areas of study by extending inquiry to the mobile app audience by exploring how Evangelical Christians actually choose and use religious mobile apps, and how app engagement informs their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 15 publications
1
12
0
Order By: Relevance
“…For example, searches conducted for apps under the term “Christian” often did not return all Christian-related apps labeled as such and available in the store database, as some previously identified apps were often absent in subsequent search lists. These inconsistencies are problematic and have been noted by other researchers, such as Bellar (2012) who found iTunes users experienced similar frustrations when searching for religious apps using the classification system and search functions provided.…”
Section: Methodsmentioning
confidence: 75%
See 1 more Smart Citation
“…For example, searches conducted for apps under the term “Christian” often did not return all Christian-related apps labeled as such and available in the store database, as some previously identified apps were often absent in subsequent search lists. These inconsistencies are problematic and have been noted by other researchers, such as Bellar (2012) who found iTunes users experienced similar frustrations when searching for religious apps using the classification system and search functions provided.…”
Section: Methodsmentioning
confidence: 75%
“…Torma and Teusner (2011) studied what happens when the cultural and social values of the iPhone intersect with religious values through specific affordances of iPhone app use. Bellar (2012) explored questions of app design in how Evangelical Christian users actually use religious iPhone apps. While these studies of app design and technological affordances are valuable, both studies noted constraints due to current iTunes categories limiting the scholar’s ability to easily identify religious apps.…”
Section: Approaches In Studying Apps and Religion In Mobile Mediamentioning
confidence: 99%
“…This echoes the dynamic, highly flexible nature of lived religion, which is distinct from religion tied to a specific community or hierarchy (Borrough & Feller, 2015). These studies of religious discourse within memes further suggest the Internet as a whole primarily promotes “lived religion” by offering resources and an environment innately resistant to the traditional boundaries of religious traditions (Bellar, 2017; Borrough & Feller, 2015). However, in this study a different structured form of religion was seen to be at work, drawing on established discourses of Civil Religion, through which arguments are intentionally and unintentionally filtered.…”
Section: Enacting Civil Religion and God Talk In Memetic Discoursementioning
confidence: 99%
“…Most of these applications and the research examining them have predominantly been on health, meditation, and physical well-being. However, some studies connect application or technology use with spirituality (see for instance Bellar 2017;Campbell 2012;Tkach 2014), though with hundreds of spiritually focused applications available in app stores for both Android and Apple smartphones (Tkach 2014), this research area has significant room for further study. As many other studies have found that applications for self-surveillance could have a significant effect on the behaviour of users (Aguilar-Martínez et al 2014;Chen, Bauman, and Allman-Farinelli 2016;Dennison et al 2013), this focus on spiritual applications seems to exemplify Foucauldian concerns about "technologies of the self," particularly as they exist between the external workings of (divine) power and reaffirmations of power through personal examination.…”
Section: Introductionmentioning
confidence: 99%